2006
DOI: 10.1103/physrevb.73.144114
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature macroscopic piezoelectricity in Nb-dopedPbZr1xTixO3ceramics driven

Abstract: The dielectric, elastic, and piezoelectric properties of a niobium-doped PbZr 1−x Ti x O 3 ceramic with a composition located near the morphotropic phase boundary have been studied from 25 to 400°C. A strong softening of the elastic coefficients was observed far below the temperature corresponding to the dielectric permittivity maximum, T max = 366°C. The steep decrease of the stiffness coefficient c 44 from 400 to 350°C is probably a stepwise anomaly which is expected at an improper ferroelastic transition. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…As expected for improper ferroelastic cubic-tetragonal and cubicrhombohedral transitions with strong coupling between symmetry breaking shear strains and the order parameter, measurements at Hz and kHz frequencies on ceramic samples with compositions close to the MPB show large (*50 %) softening of the Young's modulus, 1/S 11 , and shear modulus, G [44,[105][106][107]109]. A sample doped with Nb has also shown the same pattern of elastic softening [110]. Characteristic peaks in acoustic loss, expressed in terms of the inverse mechanical quality factor, Q À1 , show dispersion with respect to frequency and are attributed to the motion under stress of the ferroelastic twin walls [106,107,109,111].…”
Section: Strain and Elasticitysupporting
confidence: 58%
See 1 more Smart Citation
“…As expected for improper ferroelastic cubic-tetragonal and cubicrhombohedral transitions with strong coupling between symmetry breaking shear strains and the order parameter, measurements at Hz and kHz frequencies on ceramic samples with compositions close to the MPB show large (*50 %) softening of the Young's modulus, 1/S 11 , and shear modulus, G [44,[105][106][107]109]. A sample doped with Nb has also shown the same pattern of elastic softening [110]. Characteristic peaks in acoustic loss, expressed in terms of the inverse mechanical quality factor, Q À1 , show dispersion with respect to frequency and are attributed to the motion under stress of the ferroelastic twin walls [106,107,109,111].…”
Section: Strain and Elasticitysupporting
confidence: 58%
“…Reference axes, X, Y and Z, for strains of the P4mm structure are parallel to [100], [010] and [001] of the cubic parent structure. Addition of the prime for the Cm structure signifies reference axes parallel to [110], [ 110] and [001].…”
Section: Appendix: Formal Strain Analysismentioning
confidence: 99%
“…They normally have a higher permittivity, larger losses and much higher piezoelectric coupling. Among them, Nb-doped PZT (PZTN) was mostly studied [20][21][22] and due to its characteristics is commonly used for applications requiring good piezoelectric properties. This system also was chosen in this work as ferro/piezoelectric phase to form magnetoelectric ceramic composite ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, this includes the temperature during operation of piezoelectric devices, which can range from hot like in combustion engines to very cold like those occurring in aerospace applications. Recent investigations of the temperature variation of the properties of the ubiquitous piezoelectric ceramic system Pb͑Zr, TiO͒ 3 ͑PZT͒ in the range from 4.2 to 675°K have revealed that the material properties and consequently the performance of the devices at the working environment can differ significantly from those at ambient temperature.. [1][2][3][4][5] Due to the toxicity of the heavy metal lead, much effort is being put into the search of lead-free piezoelectric ceramics that can eventually replace PZT-based materials in all applications. One focus has been directed toward perovskitetype ferroelectric systems based on Bi 0.5 Na 0.5 TiO 3 ͑BNT͒, K 0.5 Na 0.5 NbO 3 ͑KNN͒, BaTiO 3 ͑BT͒, and mixed systems of these end members.…”
Section: Introductionmentioning
confidence: 99%